The Role of Cultural Identity in Shaping Political Persuasion: A Cross-Cultural Study in Indonesia and Malaysia - A. Rahman HI (PT Larva Wijaya Penerbit, 2025)
This study explores the role of cultural identity in shaping political persuasion strategies in two multicultural Southeast Asian democracies—Indonesia and Malaysia. It seeks to compare how cultural identity is articulated and utilized in political communication practices in both countries. The research adopts a qualitative comparative approach by analyzing campaign materials such as political speeches, posters, and digital content from the 2019 Indonesian and 2022 Malaysian general elections. Semi-structured interviews with political consultants and communication scholars supplement the data. Critical discourse analysis and thematic coding are used to interpret the findings. In Indonesia, cultural identity is communicated through inclusive narratives grounded in national ideology (e.g., Pancasila, gotong royong) and diverse local traditions, fostering emotional resonance across ethnic groups. In Malaysia, political communication tends to emphasize segmented cultural appeals aligned with ethnic-based party structures, indicating different modes of cultural mobilization in electoral contexts. The study reveals that cultural identity plays a significant but contextually distinct role in political persuasion within Indonesia and Malaysia. These insights enhance theoretical understanding of intercultural political communication and offer practical guidance for designing campaign strategies in culturally diverse democracies.